EOS - Environment & Oil Spill Response. An analytic tool for environmental assessments to support oil spill response planning: Framework, principles, and proof-of-concept by an Arctic example - Susse Wegeberg; Janne Fritt-Rasmussen; Kim Gustavson; Madis-Jaak Lilover; David Boertmann; Tom Christensen; Kasper Lambert Johansen; Daniel Spelling-Clausen; Frank Rigét; Anders Mosbech (Marine Pollution Bulletin, 2024)

High-resolution characterization of the development and decay of seasonal hypoxia in the Gulf of Riga, Baltic Sea - Taavi Liblik; Stella-Theresa Stoicescu; Fred Buschmann; Madis-Jaak Lilover; Urmas Lips (Frontiers in Marine Science, 2023)
The Gulf of Riga is a shallow basin in the eastern Baltic Sea connected to the Central Baltic Sea via shallow straits. Seasonal oxygen depletion occurs in the deep layer of the gulf. We conducted hourly measurements of dissolved oxygen, temperature, and salinity in the deep layer (50 m) of the gulf and observed the full cycle of development and relaxation of hypoxia in 2021. Hypoxia (<2.9 mg l -1 ) first occurred on 27 June and was observed for 71 days until its complete decay on 22 October. Average oxygen decline of 0.10 mg l -1 d -1 from saturation in mid-April until mid-July and 0.04 mg l -1 d -1 onwards until the end of August were observed. This seasonal pattern was superimposed by short-term variability in time scales from hours to days and was probably caused by inertial oscillations, (sub)mesoscale processes, deep layer currents, and pycnocline movements. Ventilation events with a relatively low impact and duration of up to ten days occurred in the deep layer due to the inflows of the saltier water from the Central Baltic. The inflowed water originated from the upper layer in winter and the thermocline in summer and was almost saturated in oxygen. Mostly mixing with existing oxygen-depleted water in the Gulf of Riga, but also local consumption declined the oxygen levels in the inflow water before it arrived at the observing station. Monthly standard deviations in oxygen varied from 0.3 to 2.8 mg l -1 and illustrated the added value of Eulerian measurements to complement the conventional monitoring.

Quasi-steady circulation regimes in the Baltic Sea - Taavi Liblik; Germo Väli; Kai Salm; Jaan Laanemets; Madis-Jaak Lilover; Urmas Lips (Ocean Science, 2022)
Circulation plays an essential role in the creation of physical and biogeochemical fluxes in the Baltic Sea. The main aim of the work was to study the quasi-steady circulation patterns under prevailing forcing conditions. A total of 6 months of continuous vertical profiling and fixed-point measurements of currents, two month-long underwater glider surveys, and numerical modeling were applied in the central Baltic Sea. The vertical structure of currents was strongly linked to the location of the two pycnoclines: the seasonal thermocline and the halocline. The vertical movements of pycnoclines and velocity shear maxima were synchronous. The quasi-steady circulation patterns were in geostrophic balance and highly persistent. The persistent patterns included circulation features such as upwelling, downwelling, and boundary currents, as well as a sub-halocline gravity current. The patterns had a prevailing zonal scale of 5–60 km as well as considerably higher magnitude and different direction than the long-term mean circulation pattern. A northward (southward) geostrophic boundary current in the upper layer was observed along the eastern coast of the central Baltic in the case of southwesterly (northerly) wind. The geostrophic current at the boundary was often a consequence of wind-driven, across-shore advection. The sub-halocline quasi-permanent gravity current with a width of 10–30 km from the Gotland Deep to the north over the narrow sill separating the Fårö Deep and Nothern Deep was detected in the simulation, and it was confirmed by an Argo float trajectory. According to the simulation, a strong flow, mostly to the north, with a zonal scale of 5 km occurred at the sill. This current is an important deeper limb of the overturning circulation of the Baltic Sea. The current was stronger with northerly winds and restricted by the southwesterly winds. The circulation regime had an annual cycle due to seasonality in the forcing. The boundary current was stronger and more frequent northward during the winter period. The sub-halocline current towards the north was strongest in March–May and weakest in November–December.

The winter stratification phenomenon and its consequences in the Gulf of Finland, Baltic Sea - Taavi Liblik; Germo Väli; Inga Lips; Madis-Jaak Lilover; Villu Kikas; Jaan Laanemets (Ocean Science, 2020)
Stratification plays an essential role in the marine ecosystem, with a shallow mixed layer being one of the preconditions for enhanced primary production in the ocean. In the Baltic Sea, the general understanding is that the upper mixed layer (UML) is well below the euphotic zone in winter. In this study, we demonstrate that wintertime shallow stratification is common in the Gulf of Finland and it forms at a depth comparable to the euphotic zone in January–February. The onset of restratification is likely associated with the annual cycle of westerly winds, which ease off in late January–early February. Stratification is first invoked along the northern coast by the westward advection of riverine water forced by easterly winds and is expanded to the south when the prevailing wind direction changes from an easterly to a westerly direction. Haline stratification emerges approximately 1 month later in the southern part of the gulf. Winter restratification can occur in the entire gulf and also in the absence of ice; thus, it is a regular seasonal feature in the area. Interannual variations in the wintertime UML correspond with variations in the North Atlantic Oscillation. Chlorophyll a concentrations in winter can be comparable to mid-summer; the limiting factor for phytoplankton bloom in winter is likely insufficient solar radiation.

Gyration effect of the large-scale turbulence in the upper ocean - Jaak Heinloo; Aleksander Toompuu; Madis-Jaak Lilover (Environmental Fluid Mechanics, 2012)

Development of a deep chlorophyll maximum of Heterocapsa triquetra Ehrenb. at the entrance to the Gulf of Finland - Kaisa Kononen; Maija Huttunen; Seija Hällfors; Patrick Gentien; Michel Lunven; Timo Huttula; Jaan Laanemets; Madis Lilover; Juss Pavelson; Adolf Stips (Limnology and Oceanography, 2003)
The development of a deep chlorophyll maximum (DCM) at a depth of 30–35 m was followed during a 15‐d case study in July 1998 at the entrance to the Gulf of Finland. The study consisted of three 18–24‐h periods of biological (chlorophyll a , phytoplankton, primary production), chemical (nitrate, phosphate) and physical (CTD, turbulence, vertical particle size distribution) measurements at an anchor station and six mesoscale towed CTD/ fluorometer mappings over the surrounding area. Exceptionally cold and windy weather led to a red tide of the dinoflagellate Heterocapsa triquetra instead of the cyanobacterial bloom that frequently occurs in late summer. Comparison of the estimated amount of nitrogen required for an H. triquetra bloom biomass with external loading affirmed that the bloom had been formed on the basis of the nitrate pool below the thermocline. The development of the bloom, therefore, led to the extremely deep nitracline. The DCM formed by H. triquetra developed at the top of the nitracline at an illumination of H. triquetra after an upwelling event that fertilized the upper layer with phosphorus.

Flow regime in the Irbe Strait - Madis-Jaak Lilover; Urmas Lips; Janek Laanearu; Bengt Liljebladh (Aquatic Sciences, 1998)